Teaching for the profession or for science, a false choice? - García-Marco, Francisco-Javier (Anuario ThinkEPI, 2011)
The impact on library and information science (LIS) education of a recent study by Richard Arum and Josipa Roksa (2011) about the acquisition of some basic competencies (critical thinking, complex reasoning, advanced writing) is discussed. Such competencies, which are very important to get the best paid jobs, must be developed through proper learning strategies: reading abundant material of the highest quality, comparing and integrating this material, applying it to new situations and problems, and appropriate written communication of ideas and findings.